Stanisław Karłowski (1879-1939): Pioneer of Biodynamic Farming and Organic Agriculture in Poland - Paull, John; Bietkowski, Pawel (Advances in Social Sciences Research Journal, 2022)
Stanisław Karłowski (1879-1939) was one of the great champions of Biodynamic farming during its formative years. After an illustrious career as an international banker, in 1920 he purchased the Szelejewo Estate in Poland comprising 1,724 hectares. Rudolf Steiner (1861-1925) presented his Agriculture Course at Koberwitz (now Kobierzyce, Poland) in the summer of 1924. Rudolf Steiner called for farming to be based on natural and biological principles and the farm to be considered as an organism. His seminal course laid the grounds for the subsequent development of Biodynamic and organic farming. Stanisław Karłowski encountered Biodynamics in 1929. He converted his Szelejewo Estate to Biodynamics, thereby creating what was, at the time, likely the largest Biodynamic (BD) farm in Europe, and perhaps the world (c.f. Ehrenfried Pfeiffer’s farm, Loverendale, Netherlands, was 320 hectares). Stanisław Karłowski published a series of seven booklets (in Polish) promoting the practice of Biodynamics (including a translation of Ehrenfried Pfeiffer); these are believed to be the first Biodynamics publications in Polish. Stanisław Karłowski ran courses on Biodynamics at his Estate and made BD preparations available. He engaged in lively debate and advocacy for Biodynamics in Poland’s ‘Agricultural Gazette’. He implemented Rudolf Steiner’s injunction to test the ideas of the Agriculture Course and he published his results and observations in ‘Demeter’, the leading Biodynamics journal of the time. With a leading Polish Anthroposophist artist, Franciszek Siedlecki, he developed advertising material for Biodynamic bread from his Szelejewo Estate. Stanisław Karłowski was a member of Rudolf Steiner’s ‘Experimental Circle of Anthroposophic Farmers and Gardeners’, the ‘inner sanctum’ of those pioneering the development of Biodynamics in its gestational years of the turbulent interwar period. He founded an association to progress biological farming practices. The breadth and depth of Stanisław Karłowski’s dedication to Biodynamics flags him as an exceptional member of the Experimental Circle. He brought to the task an economic viewpoint, the attention to detail of a banker, and the independence of thought of a non-Anthroposophist. Within weeks of the German invasion of Poland, Stanisław Karłowski was executed by a Nazi firing squad in the town square of Gostyń, his wife was deported, his beloved Szelejewo Estate was appropriated by the Nazis, and Poland was extinguished as a sovereign state. The present paper establishes Stanisław Karłowski as a pre-eminent pioneer and champion of Biodynamic and organic agriculture.